Al-Farabi: about philisophy and religion (Journal of Philosophy Culture and Political Science, 2015)
The article considers the analysis of Al-Farabi studies on religion and philosophy, their location and the importance of understanding each of them. Studied such aspects as the primary philosophy and interpretation of religion and its role in the community, a city, a virtuous religion, considered the views of other Medieval thinkers, as well as the importance of religion. Accordingly, according to the purpose of the article, the authors asked a question about the fact that how important it is to understand the distinction between religion and philosophy, as it was important at the time of writing the Al-Farabi's treatise "Books of religion", and how important it is in the modern period. The current situation in the world shows that a proper understanding of religion and philosophy can solve many problems, conflicts. To date, the relevance of philosophy and religion increases, and in this regard the works of Al-Farabi can serve as one of the basic scientific concepts.
Keywords: religion; philosophy; virtuous ruler; a virtuous city; under¬standing of the world.